Vector Network Analyzer (VNA) Measurements for Electrical Impedance Tomography - Karime Ahmad; Battistel Alberto; Möller Knut (Current Directions in Biomedical Engineering)
Electrical Impedance Tomography is a noninvasive imaging technique that employs electrical currents to reveal the internal conductivity distribution within the body. The study follows a new Radio Frequency (RF) approach, by using a Vector Network Analyzer to provide a multifrequency measurement between 10 kHz and 1 GHz. A plastic and a metallic object were positioned within a saline-filled phantom to test the EIT reconstructed images at different frequencies. The results show that based on the image reconstruction, the material’s conductivity can be distinguished at specific frequencies. However, beyond 10 MHz, the reconstructed images become less reliable until reaching 1 GHz, where the reconstructed image deteriorates significantly. While Electrical Impedance Tomography (EIT) has potential in new applications, its efficacy is limited by the ill-posed problem of the reconstruction. Further development and refinement of techniques, particularly in addressing issues that occur at higher frequencies, are required to realize EIT’s full potential in various fields.